2013
DOI: 10.1364/josab.30.003184
|View full text |Cite
|
Sign up to set email alerts
|

Tapered diode-pumped continuous-wave alexandrite laser

Abstract: We describe a low-cost and efficient alexandrite (Cr:BeAl 2 O 4 ) laser that is pumped by a high-brightness tapered diode laser (TDL). The tapered diode (TD) provides up to 1.1 W of output power and its wavelength can be finetuned to either 680.4 nm (R1 line) or 678.5 nm (R2 line) for efficient in-line pumping. Continuous-wave (cw) output powers of 200 mW, slope efficiencies as high as 38%, and a cw tuning range extending from 724 to 816 nm have been achieved. To the best of our knowledge, the cw power levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 65 publications
(105 reference statements)
3
27
0
Order By: Relevance
“…5, at crystal temperatures of 10 • C and 60 • C. The optimum wavelengths of 765 nm and 770 nm at 10 • C and 60 • C, respectively, are typical for Alexandrite [1,7,16]. Elevated temperatures extended the upper tuning range, as has been previously reported [2], but in turn increased the lower bound by 7 nm.…”
Section: Diode-pumped Wavelength Tunable Alexan-dritesupporting
confidence: 73%
“…5, at crystal temperatures of 10 • C and 60 • C. The optimum wavelengths of 765 nm and 770 nm at 10 • C and 60 • C, respectively, are typical for Alexandrite [1,7,16]. Elevated temperatures extended the upper tuning range, as has been previously reported [2], but in turn increased the lower bound by 7 nm.…”
Section: Diode-pumped Wavelength Tunable Alexan-dritesupporting
confidence: 73%
“…The cavity loss L becomes a doubly important design parameter for systems with pump ESA, with regards to slope efficiency, as it reduces both η p and η c . The trend of slope efficiency with output coupling in Figure 5 has been seen in end-pumped Alexandrite lasers [14,15], which have pump ESA [16]. In these investigations it was suggested that this could be due to energy transfer upconversion -a process that had not been identified for Alexandrite in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…The more exact formulations, (15) and (16), are also independent of σ 0 and N , assuming a suitably long gain medium and not excessive pumping (note I s is inversely proportional to σ 0 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Ti:sapphire, Alexandrite can be directly pumped with red laser diodes because its absorption band covers most of the visible spectral range [10,13]. In addition, its larger στ product [15] presents a prospect of lower laser threshold. Furthermore, a diode-pumped Alexandrite laser was shown to produce >26 W of output power in the continuous wave regime [13] which significantly exceeds output from widely used Ti:sapphire lasers.…”
Section: Introductionmentioning
confidence: 99%